Automatic energy efficiency detection and feeding device for electric cooker - ZHANG LONG; GAO SEN; LI JIAHUI; LIU YANGYUAN; WANG XIAOBO; WEN PEITIAN (2022)
The utility model provides an automatic energy efficiency detection and feeding device for an electric cooker, which is used for automatically detecting the heat efficiency of the electric cooker on line and mainly comprises a feeding part and a detection part. The feeding part comprises a ball screw mechanism, a rotating mechanism and a grabbing mechanism, the grabbing mechanism and the rotating mechanism are connected through a rod, the rotating mechanism is fixed to the ball screw mechanism, and the ball screw mechanism is fixed to the base. The detection part comprises a detection table, a positioning block and a detection mechanism, the positioning block and the detection mechanism are fixed on the detection table, and the detection mechanism is located on the detection table. According to the device provided by the utility model, the grabbing mechanism rotates to the position above the positioning mechanism from the feeding position, so that the grabbing mechanism is placed in the positioning block, the